Trânsito de potências ótimo incluindo armazenamento - Diogo Domingos Lopes de Freitas (2018)
With the growth of renewable energy sources and other distributed generation sources, energy grids are becoming more complex. Renewable production has many advantages but has the disadvantage of being very intermittent, and always requires conventional production to back it up when the weather doesn't allow for renewable production. One of the most up and coming technologies for energy grids are energy storage systems. Storage systems are gaining more importance as renewable generation increases in the electric system, and it is seen as one of the better tools to help with renewable integration, among other advantages that they can bring to the grid. In this study, the main objective was to develop a Multi-temporal Optimal Power Flow methodology, able to integrate storage and to deal with AC constraints. The multi-temporal problem formulation allows the optimization of the charging and discharging schedule, in order to evaluate the benefits of storage integration.,. The proposed approach is based on a two-blocks system. The first block uses the Matpower Optimal Scheduling Tool (MOST), responsible for the initial DC OPF and Optimization of the global dispatch for the time interval considered, while defining the storage unit charge and discharge periods that would minimize the system's dispatch. The second block is an AC OPF, applied for each hour individually, and aims at computing losses and checking all system constraints, namely reactive power flows and limits. In the last step, the AC information (losses, constraints, are re-integrated in the MOST tool, to produce the final results. The proposed methodology was validated through simulations studies on the IEEE 30 Bus Bar System. During this study, several cases of study are considered to analyse the influence of the storage unit on various aspects of the system, with the main objective being always to diminish the system's economic dispatch.